Global Perspective for Competitive Enterprise, Economy and Ecology Proceedings of the 16th ISPE International Conference on Concurrent Engineering - Chou, Shuo-Yan.; Trappey, Amy.; Pokojski, Jerzy.; Smith, Shana. (Advanced Concurrent Engineering,, 2009)
Global Perspective for Competitive Enterprise, Economy and Ecology addresses the general theme of the Concurrent Engineering (CE) 2009 Conference the need for global advancements in the areas of competitive enterprise, economy and ecology. The CE concept is based on the assumption that different components of the product life cycle should be considered together at an early stage. Its main goal is to make processes more efficient and more resistant to errors. The last twenty years have brought many changes to the organisation of product design and manufacturing narrower specialisations in engineering, the increasing presence of engineers on the global market, etc. which have led to the CE approach being able to support engineers in many different ways. As a result, the industrial presence of CE has grown to include not only implementations in well-established corporations, but also smaller applications in minor firms. The plurality of CE specialization has been reflected by the range of CE 2009 Conference tracks, which include Systems Engineering, Advanced Manufacture, Product Design, Design for Sustainability, Knowledge Engineering, Supply Chain Management, Collaborative Engineering, Web Technologies and Service Solutions. Apart from the enumerated tracks, the conference also has seven special sessions: Radio Frequency Identification, Collaborative Product Development, Multi-disciplinary Design and Optimization, Design Knowledge Utilization, Competitive Supply Chain Performance, Value Engineering and Competitive Design. The proceedings contain 84 papers, which vary from the theoretical and conceptual to the practical and industrial. The content of this volume reflects the genuine variety of issues related to current CE methods and phenomena. Global Perspective for Competitive Enterprise, Economy and Ecology will therefore enable researchers, industry practitioners, postgraduate students and advanced undergraduates to build their own view of the inherent problems and methods in CE.